Export-Growth Nexus in Nigeria: Does Capital Inflow Matters? - Adegboyo, Olufemi Samuel; Abu, Peter Katyo (Annals of Spiru Haret University. Economic Series, 2024)
This study examined how capital inflow influence export-growth nexus in Nigeria from 1980 to 2022. The study employed ADF and PP unit root test to determine the stationarity of each variable and the result reveals that there is mixed level of stationarity among the variables as gross capital formation is stationary at level while other variables such as export, capital inflow, inflation rate, and government expenditure are stationary at first difference. Consequently, the study is conducted using the ARDL estimation approach. The study found that inflation rate, gross capital creation, and trade openness had negative impacts on Nigeria’s economic growth, whereas capital inflow, government expenditure, the interaction of export and capital inflow, and trade openness all had positive impact on the economic growth. Consequently, the study recommends that government should create an enabling environment to attract more capital inflow into the country also government should review its trade policies so that export could starting stimulating economic growth in Nigeria.